2008
DOI: 10.1002/jez.b.21213
|View full text |Cite
|
Sign up to set email alerts
|

The amphioxus Hox cluster: characterization, comparative genomics, and evolution

Abstract: The amphioxus Hox cluster is often viewed as ''archetypal'' for the chordate lineage.Here, we present a descriptive account of the 448 kb region spanning the Hox cluster of the amphioxus Branchiostoma floridae from Hox14 to Hox1. We provide complete coding sequences of all 14 previously described amphioxus sequences and give a detailed analysis of the conserved noncoding regulatory sequence elements. We find that the posterior part of the Hox cluster is so highly derived that even the complete genomic sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
52
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 77 publications
(66 reference statements)
6
52
0
1
Order By: Relevance
“…This pattern suggests that repetitive sequences have been selectively excluded from the elephant shark Hox clusters. Interestingly, the density of repetitive sequences in the Hox clusters of elephant shark is similar to that in the single Hox cluster in amphioxus (3.9%), yet the elephant shark Hox clusters are 3 to 4 times smaller than the amphioxus Hox cluster (Ϸ448 kb) (11). The exclusion of repetitive sequences, therefore, does not seem to be responsible for the compact sizes of the elephant shark Hox clusters.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…This pattern suggests that repetitive sequences have been selectively excluded from the elephant shark Hox clusters. Interestingly, the density of repetitive sequences in the Hox clusters of elephant shark is similar to that in the single Hox cluster in amphioxus (3.9%), yet the elephant shark Hox clusters are 3 to 4 times smaller than the amphioxus Hox cluster (Ϸ448 kb) (11). The exclusion of repetitive sequences, therefore, does not seem to be responsible for the compact sizes of the elephant shark Hox clusters.…”
Section: Resultsmentioning
confidence: 81%
“…Recent comparative studies of Hox clusters in model genomes have shown that Hox clusters have experienced repeated molecular changes, including fragmentation, cluster duplication, gene loss, coding-sequence divergence, and cisregulatory element evolution (3-7). Because of their critical role in defining the identities of body segments, Hox genes are believed to have played a key role in driving the morphologic diversification of animals (8-10) and thus are of particular interest in understanding the genetic basis of morphologic diversity of metazoans.Among chordates, the cephalochordate amphioxus possesses a single Hox cluster (11,12). In urochordates such as Ciona and Oikopleura, the single cluster is highly fragmented and dispersed in the genome (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the incompleteness of Hox-e, -ζ, -η, and -θ loci, there is sufficient evidence that Japanese lamprey contains at least six Hox clusters. The singleton Hox4 gene in the Hox-η locus (Hox-η4) is unique in that it comprises four coding exons compared with two exons in most Hox genes and three exons in Hox13 and Hox14 genes (5,(24)(25)(26). The coding sequence of the singleton Hox4 gene in Hox-θ locus (Hox-θ4) is highly similar to Hox-η4, but its first two exons are not identifiable and the last exon contains a premature stop codon.…”
Section: Resultsmentioning
confidence: 99%
“…The intact, single Hox clusters in invertebrates are generally large (e.g., amphioxus ∼400 kb) (25), whereas gnathostome Hox clusters are more compact (∼100-210 kb) and contain very little interspersed repetitive elements (∼1-8%) (5). The four complete Japanese lamprey Hox clusters range from 145 to 526 kb and contain unusually high levels of interspersed repetitive elements (23-33%) that are higher than the overall repeat sequence content of the whole genome (21%).…”
Section: Resultsmentioning
confidence: 99%